2006
DOI: 10.1074/mcp.m600007-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic Analysis of Post-translational Modifications of Human Histones

Abstract: Eukaryote DNA is wrapped around nucleosomes that are comprised of octamers of core histones (two heterodimers of histones H2A and H2B and a heterotetramer of histones H3 and H4). Nucleosomes are joined by linker DNA and histone H1 to form chromatin. A central mechanism for regulating chromatin activity is the (reversible) covalent modification of histones by enzymes. A complex interplay between posttranslational modifications (PTMs) 1 either represses or activates transcription in a site-specific and cooperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 44 publications
3
153
0
Order By: Relevance
“…The very high methyl-accepting activity of H2B in vitro suggests that it might be a physiological substrate for PRMT7. Previous studies identified multiple post-translational modifications on human H2B, including acetylation on Lys-5, Lys-15, Lys-16, and Lys-20 (43,44), phosphorylation on Ser-14 (45), and methylation on Lys-46, Lys-57, and Lys-108 (43). However, arginine methylation on HBR has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 73%
“…The very high methyl-accepting activity of H2B in vitro suggests that it might be a physiological substrate for PRMT7. Previous studies identified multiple post-translational modifications on human H2B, including acetylation on Lys-5, Lys-15, Lys-16, and Lys-20 (43,44), phosphorylation on Ser-14 (45), and methylation on Lys-46, Lys-57, and Lys-108 (43). However, arginine methylation on HBR has not been reported to our knowledge.…”
Section: Discussionmentioning
confidence: 73%
“…They are less abundant and are more difficult to characterize because their signals are split among multiple acetylated forms (ϩ1-3 lysine-acetyl confirmed by MS/MS). The acetylations are shared among multiple sites, including Lys-11, Lys-12, Lys-15, Lys-16, and Lys-20, which are all sites that were confirmed by MS/MS in the intact form and that have previously been identified by MS in an earlier study (35). Truncations derived from two additional H2B isoforms (possibly H2B.2-E, Q16778, and H2B.1-K, O60814) were also present.…”
Section: Table I Truncated H2b Proteoforms Observed In Iipt/parallel mentioning
confidence: 75%
“…Recently, quantitative proteomic approach has revealed that treatment of human cell cultures with histone deacetylase inhibitor PXD101 leads to the expression of genes regulating growth arrest, differentiation, and apoptosis (21). In line with these studies, treatment of maspin-deficient breast cancer cell lines with trichostatin A (a histone deacetylase inhibitor) induced maspin expression in breast and bladder cancer cell lines (22,23), thus indicating that histone deacetylation may suppress maspin gene activation in these cancers.…”
Section: Maspin Gene Regulation Dna Methylation and Histone Methylamentioning
confidence: 82%
“…The ''histone code'' (constituting a combination of modifications, including acetylation, methylation, and ubiquitination) dictates chromatin structure and function during development, growth, differentiation, and homeostasis of cells (21). Recently, quantitative proteomic approach has revealed that treatment of human cell cultures with histone deacetylase inhibitor PXD101 leads to the expression of genes regulating growth arrest, differentiation, and apoptosis (21).…”
Section: Maspin Gene Regulation Dna Methylation and Histone Methylamentioning
confidence: 99%